Factors associated with spread of dengue fever in urban Lahore, Punjab, Pakistan, 2013. (March 2015) - Altaf, A
Abstract: Background: In Pakistan during 2005–06, an unprecedented increase in dengue fever occurred in the country, with a large number of cases reported in Karachi. During this time, more than 3640 patients were admitted to hospital with dengue. In the province of Punjab, disease incidence increased sharply towards August, 2011, especially in Lahore, with 17 256 cases and 279 deaths reported in that year. After Lahore, the next highest numbers of cases were reported in Faisalabad (783 cases), followed by Rawalpindi (410 cases), Pakpattan (233 cases), and Sheikhupura (225 cases). Since 2011 Lahore has been experiencing outbreaks of dengue fever every year. The aim of this study was to identify risk factors for dengue during the 2013 outbreak in Punjab, Pakistan, so as to help prevent future outbreaks. Methods: Between Oct 4 and Nov 23, 2014, we conducted a descriptive study followed by a case control study to identify the risk factors for spread of dengue fever. A case was defined as any person resident of Data Gunj Bakhsh Town who presented with fever and any three of headache, retro-orbital pain, myalgia, arthralgia, rash, haemorrhagic manifestations, leukopenia, or abdominal pain, and also laboratory confirmation through ELISA. Control participants were taken from the same town and included people with dengue symptoms, but negative ELISA results. A standardised questionnaire was developed to collect data. A line listing of cases was developed and data were analysed with EpiInfo version 7·0. Findings: We identified 147 cases and 300 controls (221 [73%] were men). Mean age was 30·9 years (range 5–70 years) and most cases were men (n=94 [64%]). Overall, the attack rate (AR) during the study period was 15 per 100 000 population. Residents in the 15–49 years age group had more dengue infections (n=114; AR=23·84 per 100 000) than did those aged 50 years and older (n=6; AR=15·3 per 100 000). On bivariate analysis, the presence of indoor stagnant water (OR=3·7 [95% CI=2.5-4.8], p<0·0001), presence of indoor larvae (OR=3·1 [2·3-4·4], p=0·001), and non-use of repellents (OR=2·7 [CI=1·5–3·2], p=0·01) were found to be independent determinants of dengue infection. Interpretation: There is a strong association between dengue transmission and both stagnant water indoors and the non-use of mosquito repellent in Punjab. That more men than women and younger rather than older people presented with dengue is consistent with other findings and may be because these groups are more likely to be outdoors and, therefore, be exposed to mosquitos. In areas at risk of dengue transmission, we undertook health education activities to improve use of repellents and remove sources of indoor stagnant water. Funding: None.